Decline in cardiorespiratory fitness and its association with vascular aging and subclinical atherosclerosis in healthy older adults: a 3-year longitudinal study - Vincent Groesser; Christopher Weyh; Torsten Frech; Natascha Sommer; Klaus Eder; Astrid Most; Samuel Sossalla; Karsten Krüger; Pascal Bauer (GeroScience, 2026)
Aging is associated with progressive deterioration of vascular function and cardiovascular risk. Cardiorespiratory fitness (CRF) is closely associated with cardiovascular health, yet longitudinal data in healthy older adults remain limited. This study examined 3-year changes in vascular and echocardiographic parameters in older adults and their associations with CRF and muscle strength. Forty-nine participants (mean age 63.8 ± 3.8 years) underwent vascular assessments (brachial/central blood pressure (BP), pulse wave velocity (PWV), augmentation index), echocardiography, CRF testing via spiroergometry to determine VO 2 peak, muscle strength testing, and carotid sonography at baseline and after 3 years. Participants were grouped by carotid plaque status: no atherosclerosis, existing atherosclerosis, or newly developed atherosclerosis. Over 3 years, CRF and muscle strength (grip strength, leg flexion) declined significantly (all p < 0.005), while systolic BP ( p = 0.042), brachial-ankle PWV ( p = 0.006), and echocardiographic parameters including aortic root diameter and ventricular dimensions increased (all p < 0.001). Participants with newly developed atherosclerosis showed the greatest CRF decline ( p = 0.012). Changes in CRF were inversely associated with changes in systolic, diastolic, and central BP (all p < 0.01). Declines in leg flexion strength were also linked to larger BP increases. Participants maintaining > 90% of baseline VO 2 peak had significantly smaller BP increases. These results indicate that vascular aging progresses measurably within a few years in clinically healthy older adults and is associated with declines in CRF and muscle strength. Preservation of CRF is linked to more favorable vascular aging profiles and a lower prevalence of newly developed atherosclerosis. Graphical Abstract

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Association of cardiorespiratory fitness level with vascular function and subclinical atherosclerosis in the elderly - Vincent Größer; Christopher Weyh; Tim Böttrich; Torsten Frech; Svenja Nolte; Natascha Sommer; Magdalena Huber; Klaus Eder; Oliver Dörr; Sophie Hoelscher; Rebecca Weber; Ebru Akdogan; et al. (European Journal of Applied Physiology, 2024)
Purpose Physical exercise is crucial for healthy aging and plays a decisive role in the prevention of atherosclerotic cardiovascular disease (ASCVD). A higher level of cardiorespiratory fitness (CRF) in the elderly is associated with lower cardiovascular and all-cause mortality. This study investigated the association of CRF level with vascular function and cardiovascular risk factors in the elderly. Methods We examined 79 apparently healthy and physically active subjects aged > 55 years (64 ± 4 years). Cardiovascular functional parameters assessed included brachial and central blood pressure (BP), pulse wave velocity (PWV), augmentation index (Aix), and ankle-brachial index. Sonography of the common carotid artery was performed. CRF level was determined by a cardiopulmonary exercise test, and everyday activity was quantified with an accelerometer. Results All participants had a higher CRF level than the reported age-specific normative values. Twenty-nine subjects had subclinical atherosclerosis of the common carotid artery. Compared with participants without atherosclerosis, they were older ( p = 0.007), displayed higher brachial systolic BP ( p = 0.006), and higher central systolic BP ( p = 0.014). Lower brachial ( p = 0.036) and central ( p = 0.003) systolic BP, lower PWV ( p = 0.004), lower Aix ( p < 0.001), lower body fat percentage (< 0.001), and lower LDL cholesterol ( p = 0.005) were associated with a higher CRF level. Conclusions In this cohort of healthy and physically active individuals, subjects with subclinical atherosclerosis displayed higher systolic brachial and central BP. A higher CRF level was associated with enhanced vascular function, consistent with an influence of CRF on both BP and vascular function in the elderly.

Association of central blood pressure with an exaggerated blood pressure response to exercise among elite athletes - Astrid Most; Lutz Kraushaar; Oliver Dörr; Stanislav Keranov; Sophie Hoelscher; Rebecca Weber; Ebru Akdogan; Vincent Groesser; Faeq Husain-Syed; Holger Nef; Christian W. Hamm; Pascal Bauer (European Journal of Applied Physiology, 2024)
Purpose The systolic blood pressure/workload (SBP/MET) slope was recently reported to be a reliable parameter to identify an exaggerated blood pressure response (eBPR) in the normal population and in athletes. However, it is unclear whether an eBPR correlates with central blood pressure (CBP) and vascular function in elite athletes. Methods We examined 618 healthy male elite athletes (age 25.8 ± 5.1 years) of mixed sports with a standardized maximum exercise test. CBP and vascular function were measured non-invasively with a validated oscillometric device. The SBP/MET slope was calculated and the threshold for an eBPR was set at > 6.2 mmHg/MET. Two groups were defined according to ≤ 6.2 and > 6.2 mmHg/MET, and associations of CBP and vascular function with the SBP/MET slope were compared for each group. Results Athletes with an eBPR ( n = 180, 29%) displayed a significantly higher systolic CBP (102.9 ± 7.5 vs. 100 ± 7.7 mmHg, p = 0.001) but a lower absolute (295 ± 58 vs. 384 ± 68 W, p < 0.001) and relative workload (3.14 ± 0.54 vs. 4.27 ± 1.1 W/kg, p < 0.001) compared with athletes with a normal SBP/MET slope ( n = 438, 71%). Systolic CBP was positively associated with the SBP/MET slope ( r = 0.243, p < 0.001). In multiple logistic regression analyses, systolic CBP (odds ratio [OR] 1.099, 95% confidence interval [CI] 1.045–1.155, p < 0.001) and left atrial volume index (LAVI) (OR 1.282, CI 1.095–1.501, p = 0.002) were independent predictors of an eBPR. Conclusion Systolic CBP and LAVI were independent predictors of an eBPR. An eBPR was further associated with a lower performance level, highlighting the influence of vascular function on the BPR and performance of male elite athletes.

Sex differences in workload-indexed blood pressure response and vascular function among professional athletes and their utility for clinical exercise testing - Pascal Bauer; Lutz Kraushaar; Oliver Dörr; Holger Nef; Christian W. Hamm; Astrid Most (European Journal of Applied Physiology, 2021)
Purpose Sex differences in blood pressure (BP) regulation at rest have been attributed to differences in vascular function. Further, arterial stiffness predicts an exaggerated blood pressure response to exercise (BPR) in healthy young adults. However, the relationship of vascular function to the workload-indexed BPR and potential sex differences in athletes are unknown. Methods We examined 47 male (21.6 ± 1.7 years) and 25 female (21.1 ± 2 years) athletes in this single-center pilot study. We assessed vascular function at rest, including systolic blood pressure (SBP). Further, we determined the SBP/W slope, the SBP/MET slope, and the SBP/W ratio at peak exercise during cycling ergometry. Results Male athletes had a lower central diastolic blood pressure (57 ± 9.5 vs. 67 ± 9.5 mmHg, p < 0.001) but a higher central pulse pressure (37 ± 6.5 vs. 29 ± 4.7 mmHg, p < 0.001), maximum SBP (202 ± 20 vs. 177 ± 15 mmHg, p < 0.001), and ΔSBP (78 ± 19 vs. 58 ± 14 mmHg, p < 0.001) than females. Total vascular resistance (1293 ± 318 vs. 1218 ± 341 dyn*s/cm 5 , p = 0.369), pulse wave velocity (6.2 ± 0.85 vs. 5.9 ± 0.58 m/s, p = 0.079), BP at rest (125 ± 10/76 ± 7 vs. 120 ± 11/73.5 ± 8 mmHg, p > 0.05), and the SBP/MET slope (5.7 ± 1.8 vs. 5.1 ± 1.6 mmHg/MET, p = 0.158) were not different. The SBP/W slope (0.34 ± 0.12 vs. 0.53 ± 0.19 mmHg/W) and the peak SBP/W ratio (0.61 ± 0.12 vs. 0.95 ± 0.17 mmHg/W) were markedly lower in males than in females ( p < 0.001). Conclusion Male athletes displayed a lower SBP/W slope and peak SBP/W ratio than females, whereas the SBP/MET slope was not different between the sexes. Vascular functional parameters were not able to predict the workload-indexed BPR in males and females.

Association of 25-hydroxy vitamin D level with the blood pressure response to a maximum exercise test among professional indoor athletes - Pascal Bauer; Lutz Kraushaar; Oliver Dörr; Timm Bauer; Holger Nef; Christian W. Hamm; Astrid Most (European Journal of Applied Physiology, 2020)
Purpose Low vitamin D levels have been associated with elevated blood pressure (BP) in the general population. However, whether there is an association of vitamin D insufficiency with BP changes during maximum exercise in athletes is currently unclear. Methods A total of 120 male professional indoor athletes (age 26 ± 5 years) were examined. BP was measured at rest and during a graded cycling test. We assessed the BP response (BPR) during maximum exercise and the respective load. BP and BPR (peak-baseline BP) were analysed with respect to 25-OH vitamin D levels, with levels < 30 ng/mL defining vitamin D insufficiency. Results 35 athletes were classified as being vitamin D insufficient. BP was not different between sufficient and insufficient vitamin D groups (122 ± 10/75 ± 7 vs. 120 ± 12/77 ± 9 mmHg). At maximum exercise, however, systolic BP (198 ± 17 vs. 189 ± 19, p = 0.026) and the pulse pressure (118 ± 18 vs. 109 ± 21 mmHg, p = 0.021) were higher in the sufficient group; the BPR was not different between groups (76 ± 20/5 ± 6 vs. 69 ± 22/3 ± 6 mmHg, p = 0.103). Athletes with sufficient levels had a higher maximum power output (3.99 ± 0.82 vs. 3.58 ± 0.78 W/kg, p = 0.015) and achieved higher workloads (367 ± 78 vs. 333 ± 80 W, p = 0.003). The workload-adjusted BPR (maximum systolic BP/MPO) was not different between athletes with sufficient and insufficient vitamin D levels (51 ± 10 vs. 56 ± 14 mmHg × kg/W, p = 0.079). Conclusion Athletes with sufficient vitamin D achieved a higher maximum systolic BP and a higher maximum power output. The workload-adjusted BPR was not different between groups, which suggests that this finding reflects a better performance of athletes with sufficient vitamin D.

The protein turnover of Arabidopsis BPM1 is involved in regulation of flowering time and abiotic stress response - Andreja Škiljaica; Esther Lechner; Mateja Jagić; Kristina Majsec; Nenad Malenica; Pascal Genschik; Natasa Bauer (Plant Molecular Biology, 2020)

Elite athletes as research model: vitamin D insufficiency associates with elevated central blood pressure in professional handball athletes - Pascal Bauer; Lutz Kraushaar; Sophie Hölscher; Shahin Tajmiri-Gondai; Oliver Dörr; Holger Nef; Christian Hamm; Astrid Most (European Journal of Applied Physiology, 2019)

Biotransformation of halophenols by a thermophilic Bacillus sp. - Uwe Michael Reinscheid; Michael Pascal Bauer; Rudolf Mller (Biodegradation, 1997)